Os silenciamentos aos sentimentos das crianças pequenas - Cavalcante, Giovana Albiero Dellosso (Universidade Federal de São Carlos, 2023)
The main objective of this study is to understand how, in early childhood education, we can educate and care from the perspective of inseparability from existence, taking into account the feelings of young children. The research uses a qualitative methodology based on the state of knowledge, and presents its results based on the field of childhood studies. During its development it is possible to find some theoretical contributions on the feeling of childhood, children's rights and childcare in early childhood education. Despite the scarcity of studies found on this subject, it was possible to draw up clues as to how children's feelings can be valued and not silenced, especially in the early childhood education environment; such as by opening up to listening and welcoming; guaranteeing children's rights; and the inseparability of educating and caring
Silencing the feelings of young children
Keywords: Sentimento; Silenciamento; Educação Infantil; Feelings; Childhood; Silencing; Early Childhood Education; Infância; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO